2022
DOI: 10.4314/jdan.v13i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of bread made from whole wheat flour and beetroot powder

Abstract: Background: Bread is one of the most popular bakery products whose consumption is increasing in many countries, including Nigeria, as a result of urbanization. This can be leveraged to develop bread with improved nutritional and health benefits. Objective: The study aimed to produce and analyze the nutritional and sensory qualities of bread made from wheat flour and beetroot powder. Materials and Methods: The research design was experimental. Samples were analyzed chemically according to the Associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
1
Order By: Relevance
“…The amount of Zn detected in the current study is higher than the levels found in bread samples fortified with beetroot powder (2-15%), as reported by Ani et al, 2022 [48]. On the other hand, the levels of Fe in the present study are lower than those reported by Ani et al, 2022 [48]. The study demonstrated that the Fe and Zn content in bread enriched with beetroot powder was lower than those in the control sample.…”
Section: Contaminantscontrasting
confidence: 84%
“…The amount of Zn detected in the current study is higher than the levels found in bread samples fortified with beetroot powder (2-15%), as reported by Ani et al, 2022 [48]. On the other hand, the levels of Fe in the present study are lower than those reported by Ani et al, 2022 [48]. The study demonstrated that the Fe and Zn content in bread enriched with beetroot powder was lower than those in the control sample.…”
Section: Contaminantscontrasting
confidence: 84%